Perjalanan dan signifikansi tahlil dalam konteks sejarah Indonesia: Warisan budaya dan perubahan sosial - Allam, Mahmud (Maliki Interdisciplinary Journal, 2024)
At the beginning of Islam entering Indonesia, there were two major religions that had spread widely in this archipelago, including Hinduism and Buddhism. Apart from these two major religions, the people of Indonesia or the people of the Archipelago also adhere to several beliefs such as animism and dynamism. Islam in Indonesia spreads its teachings in a peaceful and gentle way. Islam spread through several traders who were then continued by the scholars and also Sufi travelers. In this study, a qualitative approach was used. Qualitative research allows researchers to understand phenomena in depth and detail and is able to capture different perspectives and subjective experiences in the context of tahlil as Indonesian cultural heritage. In the data collection technique using literature studies with the aim to find out information and previous references about tahlil as a form of Indonesian cultural heritage and the social changes that occur around it. Literature sources from books, articles, journals and other related documents will be used. In conclusion, the research method on "The Journey and Significance of Tahlil in the Context of Indonesian History: Cultural Heritage and Social Change" uses a qualitative approach with data collection techniques through literature studies.